SOCIAL-POLITICAL AND ETHNIC HISTORY OF TASHKENT IN THE MIDDLE AGES - Abdurasilov Sh. R. (TARIXIY TADQIQOTLAR, 2026)
Tashkent occupies a special place in the socio-economic, cultural and spiritual development of Central Asia and has made a significant contribution to the centuries-old historical and evolutionary processes of development. There are ancient tribal settlements in this place, in particular medieval architectural monuments, as well as numerous historical, archaeological and cultural monuments preserved in Tashkent and its surroundings. The article says that Tashkent is one of the important cities of the Great Silk Road, occupying an important place in the history, economic, political, cultural and ethnic life of the peoples of Central Asia in the Middle Ages.